Natural Activators of Autophagy Increase Maximal Walking Distance and Reduce Oxidative Stress in Patients with Peripheral Artery Disease: A Pilot Study - Ombretta Martinelli; Mariangela Peruzzi; Simona Bartimoccia; Alessandra D'Amico; Simona Marchitti; Speranza Rubattu; Giovanni Alfonso Chiariello; Luca D'Ambrosio; Sonia Schiavon; Fabio Miraldi; Wael Saade; Mizar D'Abramo; et al. (MDPI AG, 2022)
Trehalose, spermidine, nicotinamide, and polyphenols have been shown to display pro-autophagic and antioxidant properties, eventually reducing cardiovascular and ischemic complications. This study aimed to investigate whether a mixture of these components improves maximal walking distance (MWD) in peripheral artery disease (PAD) patients. Nitrite/nitrate (NOx), endothelin-1, sNOX2-dp, H2O2 production, H2O2 break-down activity (HBA), ATG5 and P62 levels, flow-mediated dilation (FMD), and MWD were evaluated in 20 PAD patients randomly allocated to 10.5 g of mixture or no-treatment in a single-blind study. The above variables were assessed at baseline and 60 days after mixture ingestion. Compared with baseline, mixture intake significantly increased MWD (+91%; p < 0.01) and serum NOx (+96%; p < 0.001), whereas it significantly reduced endothelin-1 levels (−30%, p < 0.01). Moreover, mixture intake led to a remarkable reduction in sNOX2dp (−31%, p < 0.05) and H2O2 (−40%, p < 0.001) and potentiated antioxidant power (+110%, p < 0.001). Finally, mixture ingestion restored autophagy by increasing ATG5 (+43%, p < 0.01) and decreasing P62 (−29%, p < 0.05). No changes in the above-mentioned variables were observed in the no-treatment group. The treatment with a mixture of trehalose, spermidine, nicotinamide, and polyphenols improves MWD in PAD patients, with a mechanism possibly related to NOX2-mediated oxidative stress downregulation and autophagic flux upregulation. Clinical Trial Registration unique identifier: NCT04061070.